Hydrogeomorphic Wetlands Classification to Determine Ecological Functions: A Case Study of Choghakhor Wetland - Bahram Melekmohamadi; Fatemeh Jahanishakib; Ahmadreza Yavari (نشریه جغرافیا و برنامه‌ریزی, 2016)
In this study, for potential survey construction of wind power plants in the provinces of Khorasan Razavi and Northern different criteria and sub-criteria have been considered. To become fuzzy criteria are based on expert opinions and investigation done researches, control point and fuzzy function for each of the layers based on their membership gradation range of zero and one was determined in the IDRISI software. Then, according to the importance of integrating information, Analytical Hierarchy Process (AHP) for layers weighting was implemented by Expert choice software. Then, the software ArcGIS, was used to spatial analysis and overlapping layers, and after the analysis of information, Razavi Khorasan and North Khorasan province, in terms of capability the wind power plants building, divided into four levels: excellent, good, fair and poor. Finally, the results indicated that excellent are as for the construction of wind power plants in the study area are located in thesoutheast ofthe study area at Torbatjam station with an area exceeding 222565 .97 hectares (0.018 percent). In addition, good areas are located around the Taybad and Khaaf, Golmakan, Sarakhs, Roshtkhar, Bardaskan, Neyshaboor, Sabzevar, Bojnurd, Ferdows and Jajarm stations with an area exceeding 1817573 .81 hectares (0.17 percent). One cans that renewable energy of wind without any pollution could be utilized by the construction of wind power plants in the replaces ultimately.